An Evaluation Framework and Instrument for Evaluating e-Assessment Tools - Upasana Gitanjali Singh (Athabasca University Press, 2017)
e-Assessment, in the form of tools and systems that deliver and administer multiple choice questions (MCQs), is used increasingly, raising the need for evaluation and validation of such systems. This research uses literature and a series of six empirical action research studies to develop an evaluation framework of categories and criteria called SEAT (Selecting and Evaluating e-Assessment Tools). SEAT was converted to an interactive electronic instrument, e-SEAT, to assist academics in making informed choices when selecting MCQ systems for adoption or evaluating existing ones.